Detection of Influenza a Virus in Swine Nasal Swab Samples With a Wash-Free Magnetic Bioassay and a Handheld Giant Magnetoresistance Sensing System - Su, Diqing; Wu, Kai; Krishna, Venkatramana D.; Klein, Todd; Liu, Jinming; Feng, Yinglong; Perez, Andres M.; Cheeran, Maxim C.-J.; Wang, Jian-Ping (Frontiers in Microbiology, 2019)
The dissemination of Influenza A virus (IAV) throughout the world has become one of the main concerns for the health of both animals and human beings. An efficient and sensitive diagnostic tool is thus needed for the early detection of IAV. Here, we developed a wash-free magnetic bioassay and further integrated it with a handheld platform based on giant-magnetoresistance (GMR) sensors. The wash-free magnetic bioassay significantly accelerates and simplifies the detection process. This brand-new system was successful in detecting both IAV nucleoprotein and IAV-contained nasal swab samples from pigs on the farm. The extrapolated limit of detection (LOD) is 0.3 nM for IAV nucleoprotein and less than 250 TCID50/mL for IAV-spiked nasal swab samples. The detection of nasal swab samples containing unpurified IAV was also performed, demonstrating the capability of the magnetic wash-free assay in the detection of biomarkers in complex sample matrix.